Yiqi Jianpi Huayu Jiedu Decoction Inhibits Metastasis of Colon Adenocarcinoma by Reversing Hsa-miR-374a-3p/Wnt3/β-Catenin-Mediated Epithelial–Mesenchymal Transition and Cellular Plasticity - Zhuang, Yuwen; Zhou, Jinyong; Liu, Shenlin; Wang, Qiong; Qian, Jun; Zou, Xi; Peng, Haiyan; Xue, Tian; Jin, Zhichao; Wu, Cunen (Frontiers in Oncology, 2022)
Colon adenocarcinoma (COAD) accounts for 95% of colon cancer cases, with the 5-year survival rate significantly affected by local or distant metastases. Yiqi Jianpi Huayu Jiedu decoction (YJHJD), based on the theory of “nourish qi, invigorate the spleen, remove blood stasis, and detoxify”, has long been applied and shown to be remarkable in the prevention and treatment of gastrointestinal tumors. However, the underlying therapeutic mechanisms of YJHJD have not been fully elucidated. Herein, we first confirmed hsa-miR-374a-3p as a tumor suppressor based on its lower expression in the plasma of patients with COAD with liver metastasis and association with more advanced local progression. We also verified WNT3 as a potential target of hsa-miR-374a-3p and observed its increased expression in COAD tissues. Furthermore, we showed that the hsa-miR-374a-3p/Wnt3/β-catenin axis was responsible for epithelial–mesenchymal transition (EMT) and cellular plasticity in COAD, as well as poorer patient prognosis. Our results showed that YJHJD inhibited motility and colony potential in vitro, as well as liver metastasis of COAD in vivo. Moreover, YJHJD induced a reversal of EMT and cellular plasticity-related molecular expression, increased hsa-miR-374a-3p, and decreased Wnt3 and β-catenin levels. In addition, silencing of hsa-miR-374a-3p weakened YJHJD inhibition, whereas the β-catenin inhibitor XAV939 partially repaired it. Taken together, these results demonstrated that YJHJD suppressed the EMT and cellular plasticity of COAD by regulating hsa-miR-374a-3p/Wnt3/β-catenin signaling.